2011
DOI: 10.5588/pha.11.0013
|View full text |Cite
|
Sign up to set email alerts
|

Did successfully treated pulmonary tuberculosis patients undergo all follow-up sputum smear examinations?

Abstract: To assess response to anti-tuberculosis treatment as per national guidelines, a retrospective record review was undertaken in four districts of Andhra Pradesh, India, in December 2009 to determine whether pulmonary tuberculosis (PTB) patients reported as successfully treated (cured or treatment completed) underwent all scheduled follow-up sputum smear examinations. In a quarterly cohort of 3000 PTB patients reported as successfully treated, 1847 (61.5%) underwent all follow-up sputum examinations, with a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Second, our estimate of the added value of 0.9% positive sputum smears at the end of treatment might be affected by the 15% of patients who for various reasons did not undergo the last follow up smear examination at the end of treatment completion. A large number of patients not undergoing follow-up sputum smear examination is not unique to this study and/or region and has also been highlighted in another study from a different region in the country [8] . Even with a low estimate of 0.8%, obtained through the sensitivity analysis presented in the results, from a public health perspective, the absolute number in terms of cases of potentially resistant TB cases identified is still significant.…”
Section: Discussionmentioning
confidence: 85%
“…Second, our estimate of the added value of 0.9% positive sputum smears at the end of treatment might be affected by the 15% of patients who for various reasons did not undergo the last follow up smear examination at the end of treatment completion. A large number of patients not undergoing follow-up sputum smear examination is not unique to this study and/or region and has also been highlighted in another study from a different region in the country [8] . Even with a low estimate of 0.8%, obtained through the sensitivity analysis presented in the results, from a public health perspective, the absolute number in terms of cases of potentially resistant TB cases identified is still significant.…”
Section: Discussionmentioning
confidence: 85%
“…Failure to perform the control smears can bring consequences such as a delay in identifying patients who do not adhere to treatment, or do not respond to drug therapy, and can hinder early detection of bacterial multidrug resistance (14) . It is observed that the follow-up of patients with the performance of sputum smear microscopy in this study occurred in the average of 2.7 per patient, being superior, except for that of the sixth month, to those found in a study conducted in the province of Santa fé / Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, of the 196 patients monitored, the sputum smear was performed in 79.1% at the end of the second month, 57.6% by the end of the fourth month and 70.1% at six months (7) . Scholars point lack of cough or sputum of patients, incomplete or inadequate information given by the health team about the need to undergo the sputum test (14) , and the centralization of examination in reference laboratories far from the patient's home as possible reasons for the failure to undertake follow-up smear (7) . The importance of the accountability of the service that monitors the TB patient for the collection and delivery of the sample to the laboratory, which reduces travel costs for the patient and ensures the agility of operations is ratifi ed.…”
Section: Discussionmentioning
confidence: 99%
“…Once the data about publications reported in the questionnaires had been verifi ed by other means, it was found that course participants had written a further 19 papers during that subsequent year, mostly as a fi rst author and some as a co-author (Table 4): 17 of the 19 papers were published within 24 months of course end (by 1 May 2012), and two remained 'submitted'. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Participants reported 10 posters and/or oral presentations at conferences. Nine participants had been involved in OR training and/ or mentoring (fi ve as mentors in subsequent OR training activities undertaken by The Union and/or MSF), and fi ve had reviewed papers for peer-reviewed journals.…”
Section: Public Health Action Operational Research Training 94mentioning
confidence: 99%